Pengaruh Literasi Keuangan Digital dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan Pribadi Generasi Z di STIEPARI Semarang - Intan Purnama Halawa; Bayu Ade Prabowo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
Generation Z students, as digital natives, face unique challenges in personal financial management amid rapid digital financial service growth. This study examines the influence of digital financial literacy and lifestyle on personal financial management behavior among Generation Z students at STIEPARI Semarang. Using a quantitative causal approach with census sampling technique, data were collected from 29 respondents through structured questionnaires distributed online during January 19–22, 2026. Multiple linear regression analysis reveals that digital financial literacy has a significant positive effect on personal financial management behavior (β = 1.180, t = 4.991, p < 0.001), while lifestyle does not significantly influence financial management behavior (β = −0.102, t = −0.503, p = 0.619). Simultaneously, both variables significantly affect personal financial management behavior (F = 29.670, p < 0.001) with an R² of 69.5%, indicating a strong predictive model. These findings confirm the Theory of Planned Behavior and Financial Literacy Theory in the digital context, demonstrating that digital financial literacy is the dominant factor shaping Generation Z's financial management behavior. A key theoretical contribution is the confirmation that digital competency extends traditional financial literacy frameworks, while the practical contribution lies in evidence-based recommendations for curriculum integration in small private higher education institutions. Research limitations include small sample size (n = 29) and high multicollinearity between independent variables, suggesting future research should expand samples across multiple institutions and incorporate moderating variables such as financial attitude and financial self-efficacy.